2001
DOI: 10.1002/ijc.1340
|View full text |Cite
|
Sign up to set email alerts
|

Gene delivery using a receptor-mediated gene transfer system targeted to hepatocellular carcinoma cells

Abstract: For gene therapy to be effective in cancers, it is necessary to deliver therapeutic genes into cells with high specificity and efficiency. In this study, we examined the in vitro and in vivo gene delivery efficiency of a new, growth receptor-mediated gene transfer system in hepatocellular carcinoma (HCC). The effects of transfection of wild-type p53 using this system were also studied. The system consisted of a ligand oligopeptide for epidermal growth factor receptor (EGFR) recognition, a polypeptide for DNA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Overcoming a single barrier cannot necessarily guarantee the success of transfection. As reported for PLL-based vectors, gene delivery through EGF receptor-mediated internalization was inefficient without the aid of endosome-releasing agents [10,35,37], implying that the ligand and endosomolytic agents together play an essential role in PLL-mediated gene delivery. However, for vectors composed of PEI with great advantage in escaping the endosome, the incorporated EGF could make an independent contribution on increasing transfection efficiency [5,6].…”
Section: Effect Of Egf In Different Systemsmentioning
confidence: 98%
See 1 more Smart Citation
“…Overcoming a single barrier cannot necessarily guarantee the success of transfection. As reported for PLL-based vectors, gene delivery through EGF receptor-mediated internalization was inefficient without the aid of endosome-releasing agents [10,35,37], implying that the ligand and endosomolytic agents together play an essential role in PLL-mediated gene delivery. However, for vectors composed of PEI with great advantage in escaping the endosome, the incorporated EGF could make an independent contribution on increasing transfection efficiency [5,6].…”
Section: Effect Of Egf In Different Systemsmentioning
confidence: 98%
“…In Part I, this study investigates whether cellular entry is one of the main intracellular barriers to transfection in the pentablock copolymer vector systems by incorporating epidermal growth factor (EGF), a 53-residue peptide that binds to the EGF receptor with high affinity [4], into the polyplex constructs in different ways, with the aim of enhancing transfection in cancer cell lines through receptor-mediated cellular uptake. A number of studies have shown the efficacy of EGF incorporation in enhancing transfection efficiency of some polymeric vectors in tumor cells that overexpress the EGF-receptor [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, axin, an important regulator of b-catenin, is commonly mutated in human HCCs, and transduction of the wild-type Axin gene (AXIN1) induces apoptosis in HCC cells as well as in colon cancer cells. Other gene therapy possibilities against cancer have been reported by administration of a recombinant adenoviral vector expressing wild-type tumor suppressor p53 gene [58].…”
Section: Apoptosis-related Gene Therapy Against Cancermentioning
confidence: 99%
“…Towards this target, several approaches have been made [164][165][166][167][168][169]. Herpes virus simplex type-1 (HSV-1) is one of the most promising viral platforms for transferring therapeutic genes and the development of oncolytic vectors that can target, multiply in, and eradicate hepatoma cells via their lytic cycle.…”
Section: Inhibition Of Oncogenes and Restoration Of Tumor-suppressor mentioning
confidence: 99%